Assessment of needs in residential care: perspectives of youth and professionals - Calheiros, M. M.; Patrício, J. (Journal of Child and Family Studies, 2014)
The evaluation and identification of needs profiles for youth in residential care, through qualitative and quantitative methodologies involving different stakeholders, are still relatively uncommon, even though they are essential in developing specific and effective services. This article will present two studies, one with youth and another with professionals. To assess needs from the standpoint of youth, four focus groups were held with youth in residential care (n = 21). To identify needs profiles of youth from the standpoint of professionals, 47 professionals evaluated a sample of youth in residential care (n = 110) using the RCYNA questionnaire. The results of the study with youth point to needs in three main areas: living situation, social and family relationships, and education. The results of the study with professionals reveal three needs profiles with distinct risk levels: low risk, without emerging needs; intermediate risk, with needs in terms of the economic and living situation; and high risk, with needs in terms of relationships, behavioural, psychological and emotional skills, and education and employment.